2008
DOI: 10.1159/000112841
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the ‘Shoulder-Umbilical’ Distance for Insertion of Umbilical Catheters in Newborn Babies: Questionnaire Study

Abstract: Approximately 40 years ago, Dr. Peter Dunn introduced a simple method to determine the insertion length of umbilical catheters in neonates, by using the ‘shoulder-umbilical’ (S-U) length. Since then, various studies have reported a high rate of malposition of umbilical catheters. One of the possible reasons is that the method used to determine the S-U length varies among paediatric professionals. We performed a questionnaire study among 101 paediatric professionals in the Netherlands and found that the method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 7 publications
0
14
0
2
Order By: Relevance
“…While the shoulder-umbilicus length is frequently used to estimate the insertion depth of umbilical catheters, it appears that many clinicians do so incorrectly. A survey of 101 paediatric doctors, including 45 consultant paediatricians, showed that only 14/101 (14%) used the measurement described by Dunn correctly 30. Our results should be extrapolated with caution if the shoulder-umbilicus length is measured incorrectly.…”
Section: Discussionmentioning
confidence: 64%
“…While the shoulder-umbilicus length is frequently used to estimate the insertion depth of umbilical catheters, it appears that many clinicians do so incorrectly. A survey of 101 paediatric doctors, including 45 consultant paediatricians, showed that only 14/101 (14%) used the measurement described by Dunn correctly 30. Our results should be extrapolated with caution if the shoulder-umbilicus length is measured incorrectly.…”
Section: Discussionmentioning
confidence: 64%
“…[3][4][5] Several studies have questioned the current methods used for estimating umbilical catheter insertion length. Lopriore et al 6 questioned 101 pediatric professionals from 6 centers in the Netherlands and found that the method used by the participants to measure the shoulder-umbilicus length was highly inconsistent, with only 14% using the described measurement. BW-based methods that are widely used in the United States do not predict catheter placement as accurately in smaller preterm infants.…”
Section: Introductionmentioning
confidence: 99%
“…All these approaches required the patient to remain anaesthetised during the islet delivery and repeated infusions were not feasible as the veins could not be safely exteriorised for prolonged periods even using an omental tube. The umbilical vein as a method of portal venous access has been long used for total parenteral nutrition in neonates (where the vein is still patent) or occasionally in adults with difficult vascular access problems [18]. The use of the recanalised umbilical vein overcame the obstacles associated with the middle or right colic vein.…”
Section: Discussionmentioning
confidence: 99%